Preliminaries of the government of the Río de la Plata. Correspondence of Pedro Esteban Dávila with the court administration, between his appointment and his arrival in Buenos Aires (1629-1631) - Amadori, Arrigo (2024)
This article analyzes correspondence sent by the field master Pedro Esteban Dávila to various levels of court administration, from his appointment as governor of Buenos Aires until his arrival in the Río de la Plata. These writings, sent between 1629 and 1631 from Lisbon and Rio de Janeiro, reveal some little-known aspects, at least for this region, of the efforts of a royal servant who, even before leaving the peninsula, played an essential role in the configuration of defensive devices for an enclave of geopolitical relevance at a critical juncture. Furthermore, this repertoire of letters provides an experiential perspective on the functioning of a composite monarchy during the period of the Union of Crowns.